Possible mechanisms of hypercholesterolemia and clinico-prognostic effects of lipid-lowering therapy in patients with coronary heart disease. (Literature review and original data analysis) - A. P. Vasilyev; N. N. Streltsova; M. A. Sekisova; Yu. N. Senatorov; I. A. Maltseva (Российский кардиологический журнал)
In this article, possible ways of hypercholesterolemia development are analyzed. The authors discuss the role of cell membrane function in cholesterol homeostasis. Taking into account structural and functional stabilization of biomembranes, lipidlowering and pleiotropic effects of statins are analyzed. Association between blood cholesterol level and coronary heart disease (CRT)) prognosis, possibly of indirect nature, is discussed.